PROGRAM BANTUAN LANGSUNG SEMENTARA MASYARAKAT (BLSM) DI NAGARI BUAYAN LUBUK ALUNG KECAMATAN BATANG ANAI KABUPATEN PADANG PARIAMAN - Melisa Putri, Dian; Rianto, M.Pd, Slamet; Prari Keslan, Rozana Eka (Pendidikan Geografi, 2014)
ABSTRACTÂ This research is intending to obtain information about the Temporary Funding Program (BLSM) for citizen of Nagari Buayan Lubuk Alung sub-district of Batang Anai regency of Padang Pariaman.Kind of research is a qualitative. The informant consists of local residents whose accept and whose do not receive the BLSM. The researchist is using Snow Ball Sampling Technic to specify the informant. The Place of research is Nagari Buayan Lubuk Alung sub-district of Batang Anai regency of Padang Pariaman. The Data has been accumulated through observation, interviews, and documentation process.And the results of research as follows: 1) The ability of BLSM in reducing poverty has not reached the expectations, the fund which received by people is deficient compare to their live needs. And the distribution of fund to destitute people has been running smoothly and appropriate to, even thought itâs still not spread evenly. Time of distribution does not follow the schedule that assigned by government. 2) Mechanisms schedule which Badan Urusan Logistik has been assigned for BLSM does not match with condition ofÂ  Bulog which has been assigned for once a month. While the actual of distribution is twice a month 3) People whose received BLSM appraise it as a positive way to reduce their household costs. People was cynical because of the division BLSM data does not match the data obtained, but here there is an element of family division BLSM it self.